1998
DOI: 10.1074/jbc.273.7.3838
|View full text |Cite
|
Sign up to set email alerts
|

Indole-3-carbinol Inhibits the Expression of Cyclin-dependent Kinase-6 and Induces a G1 Cell Cycle Arrest of Human Breast Cancer Cells Independent of Estrogen Receptor Signaling

Abstract: Indole-3-carbinol (I3C), a naturally occurring component of Brassica vegetables such as cabbage, broccoli, and Brussels sprouts, has been shown to reduce the incidence of spontaneous and carcinogen-induced mammary tumors. Treatment of cultured human MCF7 breast cancer cells with I3C reversibly suppresses the incorporation of [ 3 H]thymidine without affecting cell viability or estrogen receptor (ER) responsiveness. Flow cytometry of propidium iodide-stained cells revealed that I3C induces a G 1 cell cycle arres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
182
2
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 248 publications
(198 citation statements)
references
References 52 publications
(51 reference statements)
12
182
2
2
Order By: Relevance
“…46 It is noteworthy that previous reports have demonstrated that I3C inhibited CDK6 expression in both estrogen-responsive and nonresponsive human breast carcinoma cells. 19,21 Those observations, in combination with our studies involving LNCaP prostate carcinoma cells, suggest that the selective inhibition of CDK6 gene expression may be a hallmark of the cellular mechanism operating in reproductive tumor cells that allows these cell types to respond to I3C. In breast carcinoma cells, we have discovered that I3C treatment alters the function of Sp-1 transcription factors at the specific indoleregulated composite element in the CDK6 promoter, 21 and we currently are attempting to determine whether I3C has a similar response in human prostate carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…46 It is noteworthy that previous reports have demonstrated that I3C inhibited CDK6 expression in both estrogen-responsive and nonresponsive human breast carcinoma cells. 19,21 Those observations, in combination with our studies involving LNCaP prostate carcinoma cells, suggest that the selective inhibition of CDK6 gene expression may be a hallmark of the cellular mechanism operating in reproductive tumor cells that allows these cell types to respond to I3C. In breast carcinoma cells, we have discovered that I3C treatment alters the function of Sp-1 transcription factors at the specific indoleregulated composite element in the CDK6 promoter, 21 and we currently are attempting to determine whether I3C has a similar response in human prostate carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Equal amounts of total cellular protein were mixed with loading buffer (25% glycerol, 0.075% SDS, 1.25 mL 14.4 M 2-mercaptoethanol, 10% bromophenol blue, 3.13% stacking gel buffer), fractionated by electrophoresis on 10% polyacrylamide/0.1% SDS resolving gels, electrophoretically transferred to nitrocellulose membranes, and prepared for Western blotting as described previously. 19,20 The working concentration for all antibodies was 1 g/mL and immunoreactive proteins were detected after 1-3 hours of incubation at room temperature with the appropriate horseradish peroxidaseconjugated secondary antibodies. Blots were treated with ECL reagents (NEN Life Science Products), and all proteins were detected by autoradiography.…”
Section: Western Blot Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…It can inhibit cell cycle progression, induce apoptosis, and inhibit tumour invasion and metastasis, even in ER-a-negative cells (Meng et al, 2000a(Meng et al, , 2001Bonnesen et al, 2001;Chen et al, 2001). Indole-3-carbinol downregulates expression of a G1 cyclindependent kinase (CDK6) and upregulates a CDK inhibitor (p21 Cip1 ) (Cover et al, 1998). The major active metabolite of I3C, diindolylmethane (DIM), induces expression of GADD45a, a DNA damage-responsive gene and putative tumour suppressor (Carter et al, 2002).…”
mentioning
confidence: 99%